Final detailed design of an all-in-one attachment-based PHC pile head cutting robot and its structural stability analysis. Issue 5 (3rd September 2021) - Hwang, Ji-Young; Yeom, Dong-Jun; Kim, Jun-Sang; Kim, Young Suk
ABSTRACT: Conventional pretensioned spun, high-strength concrete (PHC), pile head cutting process is associated with safety, quality uniformity, and labor productivity problems. However, trend analysis has revealed that no technology has been developed to address these problems as these pertain to specific Korean construction site situations. This study aims to derive the final detailed design for an all-in-one attachment-based PHC pile head cutting robot, and analyzes its structural stability. To this end, the key functions of an all-in-one attachment-based PHC pile head cutting robot have been defined, and the related core element technologies have been analyzed. This has led to the presentation of two detailed design alternatives. Both of these were then subjected to an analytical hierarchal process (AHP) and trade-off analysis that led to the final selection of the diamond wheel saw-based detailed design. In a structural stability analysis of the final detailed design, all tested parts did not surpass the threshold yield strengths of 230 MPa (SS400) and 255 MPa (AL6061 T6). If a prototype is developed based on the final detailed design derived in this study, it is expected to have improved work safety, quality uniformity, and work efficiency characteristics compared with the conventional PHC pile head cutting process.